Demographics, clinical features and outcome of COVID-19 patients admitted to tertiary care hospital. - Jagadevi; A Sumanta; DS Shubh; KS Sudhindra; B Saipriya (Tropical Journal of Pathology and Microbiology, 2022)
Background : In December 2019, a novel coronavirus (SARS-CoV-2) emerged in China and rapidly spread globally including India and has presented major challenges to health care settings, clinical laboratories, from initial diagnosis to patient monitoring and treatment. The characteristic demographic, clinical observations and outcomes of Novel Coronavirus disease 2019 (COVID-19) have been reported from different countries.  Objectives: The present study was aimed to describe the clinical and demographic characteristics and outcomes of COVID-19 patient. Materials and methods: This retrospective study was conducted for a period of six months from September 2020 to February 2021 at Microbiology Department, Molecular laboratory Basaveshwara medical college and hospital(BMCH),Chitradurga. All clinically suspected RTPCR positive COVID-19 Patients aged more than 18 years admitted in COVID Care centre,BMCH were  included in the study. Demographic, clinical, laboratory, treatment and outcome data were extracted from hospital medical records section and analysed. Results:  Total of 1368 RTPCR positive COVID-19 patients data were analysed. The mean age of all patients was 38.9 years (± 12.5 SD). Males(59.3%) were slightly higher in number than females (40.6%). Co-morbidities associated with COVID-19 were, Hypertension in 268(19.5%), diabetes in 238 (17.3%),COPD in 84(6.1%), chronic kidney disease  in 34 (2.4%) and chronic liver disease  in 19 (1.3%) patients. Of the 1368 COVID-19 patients, 723(  52.9% ) were asymptomatic, 645( 47.2%) symptomatic , 289 (21.1%)  patients  had  intensive care unit (ICU)admission,1084(79.2%) cured  from COVID-19 and discharged and 191(13.6%) cases had mortality. Conclusion: The observation from our study suggests  that more number of asymptomatic patients with COVID-19  and patients with comorbidities were more vulnerable to disease severity and critical condition.  Early categorisation of patients and management based on set protocol resulted in good outcomes and low mortality of cases.